Bridging Internal Constraints and Performance: A SEM-PLS Analysis of Public Infrastructure Projects in the Buton Islands - Bahar, Syamsul Bahri; Efendi, Ahmad; Agusman; Idwan; Makmur, Muammar; Sunik (Journal of Novel Engineering Science and Technology, 2025)
Public infrastructure projects in developing regions often face performance issues due to internal capacity gaps and weak management systems. This study emphasizes both the direct and mediating effects of internal factors on project outcomes, with stronger justification for using SEM-PLS and additional comparative methods. Regression-based robustness checks and PLSpredict cross-validation are incorporated to validate the results. The research investigates the mediating role of construction management in linking internal organizational factors to project performance in the Buton Islands, Southeast Sulawesi. Key elements examined include planning quality, supervisory practices, communication effectiveness, and equipment readiness, measured against cost, time, and quality outcomes. A quantitative design using Structural Equation Modeling with Partial Least Squares (SEM-PLS) was applied to data from 54 construction professionals in government and private sectors. To address statistical concerns with the small sample size and many indicators, redundant items were eliminated (loading < 0.70), and discriminant validity was tested using HTMT ratios. Findings indicate that internal organizational conditions have a moderate but significant direct effect on project performance, while this influence is substantially strengthened when mediated by effective construction management. Novelty is underscored by situating the analysis in the Buton Islands, a geographically isolated and resource-constrained region rarely studied in international literature, extending systems theory and the Iron Triangle to new environments. The strongest predictive paths involve budgeting systems, scheduling mechanisms, and quality assurance frameworks. Beyond technical dimensions, managerial practices also foster institutional trust and resilience, offering practical guidance for policymakers and practitioners.